National assessment of foreign languages in Sweden: A multifaceted and collaborative venture. (July 2022) - Erickson, Gudrun; Borger, Linda; Olsson, Eva
The article addresses the local system of national assessment of foreign languages in Sweden, a contextually specific, large-scale system with a summative aim, but also a system aimed to support teachers in their continuous assessment and grading of their students' competences. In the text, the educational context and the multifaceted nature of national assessment are described and discussed. Furthermore, based on a broad view of validity with use and consequences in focus, different, and partly interwoven, aspects of collaboration in test development are exemplified and discussed, including policy, stakeholders, and research. Special attention is given to contributions by stakeholders, in particular students and teachers. Their involvement is regarded as a central component in the test development process, not only because it widens, deepens, and further develops the competences needed, but also because it increases the possibility to affect and enhance the use of the materials for the justice and beneficence of test-takers and society at large—aspects at the heart of validity. It is emphasized that collaboration requires sensitivity and sensibility from those involved to optimize overall quality and generate reciprocal benefits for all parties.